Periostin predicts all-cause mortality in male but not female end-stage renal disease patients on hemodialysis - Li, Xitong; Liu, Yvonne; Hocher, Johann-Georg; Chu, Chang; Reichetzeder, Christoph; Kalk, Philipp; Szakallova, Angelika; Chen, Xin; Krämer, Bernhard; Tepel, Martin; Hocher, Berthold (Cardiorenal Medicine, 2024)
Introduction: Periostin is a matricellular protein. Elevated serum concentrations of periostin have been reported in patients with various cardiovascular diseases, including heart failure. Patients with end-stage renal disease have a substantially increased risk for cardiovascular diseases. However, there is a lack of clinical studies to clarify the prognostic significance of systemic periostin on all-cause mortality in patients with end-stage renal disease on hemodialysis. Methods: 313 stable end-stage renal disease patients were recruited and followed for 5 years concerning all-cause mortality. At baseline, we collected blood samples and clinical data. Serum periostin concentrations were measured using a certified ELISA. Results: The optimal cut-off value for serum periostin regarding all-cause mortality, calculated through receiver operating characteristic analysis, was 777.5 pmol/L. Kaplan-Meier survival analysis using this cut-off value demonstrated that higher periostin concentrations are linked to higher all-cause mortality (log-rank test: p = 0.002). Subgroup analysis revealed that serum periostin concentrations only affected all-cause mortality in male but not in female patients (p = 0.002 in male patients and p = 0.474 in female patients). Multivariate Cox regression analyses, adjusted for confounding factors, likewise showed that elevated serum periostin concentrations were positively associated with all-cause mortality in male (p = 0.028) but not in female patients on hemodialysis (p = 0.313). Conclusion: Baseline serum periostin is an independent risk factor for all-cause mortality in male patients with chronic renal disease on hemodialysis. Periostin is a matricellular protein expressed in multiple tissues of the cardiovascular system, including the heart. Elevated serum concentrations of periostin have been documented in conditions such as heart failure, coronary artery disease, and stroke. Individuals with end-stage kidney disease (ESKD) face a significantly heightened risk of cardiovascular diseases. However, there is a dearth of clinical studies elucidating the prognostic significance of systemic periostin with respect to all-cause mortality in ESKD patients undergoing hemodialysis. Consequently, we conducted a prospective observational study on a cohort of ESKD patients, tracking their outcomes over a span of 5 years.In summary, our investigation establishes that serum periostin serves as an independent risk factor for all-cause mortality among male patients undergoing hemodialysis for chronic kidney disease. Notably, the impact of serum periostin concentrations on all-cause mortality is observed solely in male patients, with no corresponding effect in female patients. We provide a comprehensive discussion elucidating the reasons underlying this pronounced gender dependence.